Performance of the FIB-4 index in esophageal varices screening in patients with the diagnosis of liver cirrhosis - Cá Lamo-Guzmá N, Bernardo (2020)
INTRODUCTION: The diagnosis of esophageal varices in cirrhotic patients is made by the upper gastrointestinal endoscopy. Multiple non-invasive predictors have been studied for the diag-nosis of esophageal varices. The objective of this study is to testthe FIB4 index as screening of esophageal varices in patients with liver cirrhosis. MATERIALS AND METHODS: A cross-sectional analytic study was developed in four national hospital using hepatic cirrhosis patient's medi-cal files. We assessed the information using univariate and bivariate analysis, sensitivity, speci-ficity, predictive positive and negative value, the positive and negative likelihood ratio calcu-lation of the esophageal varices screening and its size. We built ROC curve for every analysis group. RESULTS: The study included 289 liver cirrhosis patients. Most of the patients were male (54.33%). 77.85% patients had esophageal varices. The distribution of varices was 19.03%, 35.99% and 22.84% for large, medium and small varices, respectively. In the FIB-4 index analysis for the presence of varices, it was found a sensitivity of 81.3%, specificity of 37.5% (AUC: 0.57). The calculation for variceal size showed a sensitivity of 81.8%, specificity of 23.9% (AUC: 0.50). In the analysis of FIB-4 index for prophylaxis groups was found a sensitivity of 81.8% and a specificity of 28.5% (AUC: 0.54). CONCLUSIONS: The FIB-4 index has no good performance in the screening for the presence of esophageal varices and its size in liver cirrhosis patients.